Alta proporção de bovinos e ovinos soropositivos e portadores renais de Leptospira sp. sob condições semiáridas - Pimenta, C. L. R. M.; Bezerra, C. S.; Morais, D. A.; Nogueira, D. B.; Silva, M. L. C. R.; Costa, D. F.; Alves, C. J.; Santos, C. S. A. B.; Higino, S. S. S.; Azevedo, S. S. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
The development of cattle and sheep farming is of paramount importance for Brazilian agriculture. Leptospirosis is caused by bacteria of the genus Leptospira sp. and stands out as causing serious reproductive problems in ruminants.